Strategic Significance: Unveiling the Dominant Role of Social Media as a Primary Marketing Tool in Digital Business Strategies - Prakosos, Riyan Dwi Yulian; Ukar, Kurweni; Astutik, Wahyuni Sri (ADMAN: Journal of Contemporary Administration and Management, 2024)
The advancement of digital technology has fundamentally altered the way companies operate. Amidst this transformation, social media has emerged as one of the key forces driving change. The aim of this research is to uncover the dominant role of social media as a primary marketing tool in digital business strategies. The methodology of this research is a qualitative literature review drawing data from Google Scholar from 2012 to 2024. The study findings indicate that social media not only enables businesses to directly connect with their audience but also facilitates deep interactions, strengthens brands, provides valuable insights, and fosters beneficial collaborations. With its ability to create emotional connections, build strong brand identities, and optimize consumer experiences, social media has become an inevitable force in the modern marketing landscape.